Keyless signature infrastructure solution for cloud attacks - Chandran, Remya; A. Sasi Kumar, Dr (International Journal of Engineering and Technology, 2018)
Keyless Signature Infrastructure (KSI) is a procedure that is used to distribute and verify the signature; only hash function cryptography is being used in this method. KSI uses block chain technology for the signing and verification of the signature. The paper will discuss the solution of different cloud attacks using Keyless Signature Infrastructure.Â Â